Implementation of an inter - carrier interference self - cancellation technique for OFDM system in altera CYCLONE 11 FPGA - Sharifah Kamilah Syed Yusof, author; Nasir Shaikh Husin, author; M. F. Jamadi, author; Nosheila Faisal, author; Mazlina Esa, author; M.H. Mamat, author; International Conference on Knowladge Based Development (2008 : Saudi, Arabia) (Skudai : Universiti Teknologi Malaysia, 2007)
PSZJBL